EFFICACY OF FUNCTIONAL ENDOSCOPIC SINUS SURGERY(FESS) IN TREATMENT OF POST NASAL DRIP (PND) AS AN ANCILLARY PROCEDURE: A COMPARATIVE STUDY - Niazi, Saleem Asif; Maqbool, Shahzad; Khan, Zafar Ullah; Hakim, Abdul; Aasim, Muhammad Umair; Maqsood, Shahid; Riaz, Yousra (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess efficacy of functional endoscopic sinus surgery (FESS) in treatment of postnasal drip (PND) as an ancillary procedure to Septoplasty with Turbinoplasty.Study Design: Quasi experimental study.Methodology: Sample size was n-200, Patients were placed in two groups Group A (n-126) had septoplasty with turbineplasty. Group B (n-74) included patients with Septoplasty and Turbinoplasty combined with functional endoscopic sinus surgery. Post operative results regarding postnasal drip were compared amongst the Two groups.Results: Data was analysed in SPSS-17, Septoplasty along with turbinectomy was performed in n-126 patients (group A). And septoplasty, turbinectomy along with functional endoscopic sinus surgery was performed in n-74 patients (group B). Post nasal drip was significantly reduced in group B at 3 months follow up (p